Language Style in Destin Daniel Cretton’s Just Mercy Movie (2019) - Naely Rizki (Metaphor, 2021)
This research discusses the language style used by the main character in Just Mercy movie (2019). The aims of this research are to explain the types of language style in Just Mercy movie (2019) and to explain the social factors which influence the main character use the language style. The researcher applied language style theory by Joos. The method of this research is descriptive qualitative research. The data are taken from the utterances of the main character in Just Mercy movie (2019). In collecting data, the techniques applied by the researcher are watching, reading, identifying, classifying, and selecting. The data analysis method is done by displaying, explaining, and interpreting. The result shows that the researcher has found all types of language style. The most dominant language style that used by the main characters is casual style. Holmes’ theory of social factors is also used in this research. The result shows that the factors participant, setting, topic, and function influence the use of language style.